To Draw Is Human: Toward No-Code Subgraph Search. - BHOWMICK, SOURAV S.; BYRON CHOI (Communications of the ACM, 2023)
This article proposes a solution to the existing visual query interface (VQI) setbacks with a plug-and-play method and blending visual query formulation with query processing. While VQIs contribute to the no-code or low-code frameworks necessary to counteract the worldwide developer shortage, talent gap and budgetary constraints they traditionally require high creation and maintenance costs, poor portability, and lack of support for subgraph query formation.